2015
DOI: 10.1111/tmi.12538
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and community effectiveness of larvivorous fish for dengue vector control

Abstract: Abstractobjective To evaluate the efficacy and community effectiveness of larvivorous fish for the control of dengue vectors and dengue transmission, when used as a single agent or in combination with other vector control methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 25 publications
(94 reference statements)
0
46
0
Order By: Relevance
“…Integrated vector control strategies (details in Table 1) were assessed in 9/13 systematic reviews (16 study arms). Entomological indices were reported on in all nine reviews [16, 1821, 23, 25, 27, 28] while only two reviews [25, 27] reported on dengue cases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Integrated vector control strategies (details in Table 1) were assessed in 9/13 systematic reviews (16 study arms). Entomological indices were reported on in all nine reviews [16, 1821, 23, 25, 27, 28] while only two reviews [25, 27] reported on dengue cases.…”
Section: Resultsmentioning
confidence: 99%
“…Han and colleagues assessed the effect of larvivorous fish (single or multiple species) in water storage containers based on ten studies [25]. Two studies were pre-post comparisons and eight studies had contemporary comparators (though were not randomised), providing very low quality evidence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 In order to achieve effective dengue control, larval source reduction with community participation should be carried out. Research has shown that for any community participation to be successful, the key is to bring about a behavioural change among the residents of the community.…”
mentioning
confidence: 99%